Rice straw valorization for bioenergy potential in Southeast Asia: a brief review on life cycle assessment (LCA) perspective - Rihana Firdaus,; Siti Norliyana Harun,; Marlia M. Hanafiah,; Peer Mohamed Abdul,; Irfana Kabir Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The large amount of rice straw production in Southeast Asia presents both challenges and opportunities for sustainable environmental management. Improper rice straw management poses significant environmental challenges, prompting interest in utilizing it for bioenergy production as a sustainable solution. However, a comprehensive understanding of the environmental implications throughout the entire lifecycle of rice straw utilization is poorly understood. A comprehensive approach of life cycle assessment (LCA) could provide valuable information concerning the environmental impact of rice straw utilisation for bioenergy. Therefore, this study attempts to provide a brief overview of the LCA of rice straw utilisation as a source of bioenergy in Southeast Asia. Several search engines and databases, including Springer, Web of Science, and Scopus, were used to select the articles for this review. These searching strategies involve three main processes: identification, screening, and eligibility. Following those process, a total of 13 articles were included in this review. The findings indicated that biochemical conversion pathways for producing bioethanol and biogas yield the greatest environmental benefits notably through greenhouse gas emissions reduction. This highlights the potential of rice straw bioenergy as a promising avenue for mitigating the impacts of climate change by curbing GHG emissions. In summary, this research underscores the significance of comprehending the holistic environmental implications of rice straw utilization for bioenergy, emphasizing the potential of specific conversion pathways to contribute to sustainable rice straw management and climate change mitigation in Southeast Asia, encouraging further research in this field for practice refinement and widespread adoption.